KEMAMPUAN TENDANGAN MAWASI GERI PADA EKSTRAKURIKULER KARATE DI SMP NEGERI 2 SINTANG - Santi Septiyani; Victor G. Simanjuntak; Eka Supriatna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The Problem In This Is How Much The Ability To Control Mawasi Geri Kicks. The Purpose Of This Research Is To Determine The Level Of Students Ability To Perform Mawasi Geri Kicks At SMP Negeri 2 Sintang. This Research Method Is Quantitative Descriptive Research Using Survey Methods With Test And Measurement Techniques. The Population In This Students Research Was 25 Samples.. The Sample Must Warm Up First, After That The Sample Performs A HIP Flexion Movement With A Distance Of 25m And Then The Sample Performs A Mawasi Geri Kick. Event Pa This Study Has A Norm Of Kick Scoring An Athlete Mawasi Geri Kick Consisting Of Scores, Categories, Sons And Daughters. The Results Of The Research And Discussion Can Be Concluded As Follows : Excellent Category Of 2 People Or 8% , Good Category Of 5 People Or 20% , Enough Categories Of 2 People Or 8% , Categories Of Less 11 People Or 44% And Categories Of Very Poor 5 People Or 20%. Keywords: Ability, Geri Mawasi Kick